Effect of cimetidine on upper gastrointestinal bleeding after renal transplantation: a prospective study. Issue 6453 (3rd November 1984) - Walter, S; Thorup Andersen, J; Christensen, U; Løkkegaard, H; Kjersem, H; Dahlager Jørgensen, J I; Stadil, F
Abstract : In 97 consecutive patients undergoing renal transplantation the incidence of upper gastrointestinal bleeding was registered over 180 days after allocation to treatment with either cimetidine or placebo. Bleeding episodes occurred in 12 patients, 11 of whom were receiving placebo and only one cimetidine (p less than 0.01). All bleeding episodes occurred during the first month after allotransplantation. Treatment with cimetidine did not lead to an increased incidence of rejection of the allograft. It is concluded that cimetidine is effective and safe in protecting against upper gastrointestinal bleeding after renal transplantation.